Cross-Cultural Collaboration in Education : Challenges and Opportunities for International Learning Programs - Adebayo Adekunle; Chimamanda Eze; Olumide Afolayan (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
This article investigates the challenges and opportunities involved in cross-cultural collaboration within international learning programs. By evaluating student exchange programs, online international collaborations, and global university partnerships, the research highlights the benefits and obstacles of fostering intercultural understanding and global competence. The findings suggest that cross-cultural education is crucial for developing global citizens and promoting international cooperation in academic settings.